A Study on Demonetization of Currency and Its Impact on Banking Sector - Gupta, Nidhi; Gupta, M. K. (Journal of Commerce and Trade, 2018)
Demonetisation is a situation where the Central Bank of the country (Reserve Bank in India) withdraws the old currency notes of certain denomination as an official mode of payment. On 8 November 2016, the Government of India announced the demonetisation of all Rs. 500 and Rs. 1000 banknotes of the Mahatma Gandhi Series. The government claimed that the action would curtail the shadow economy and crack down on the use of illicit and counterfeit cash to fund illegal activity and terrorism. The sudden nature of the announcement and the prolonged cash shortages in the weeks that followed created significant disruption throughout the economy, threatening economic output.the excess deposits accrued to the banking system due to demonetisation range between Rs 2.8-4.3 trillion “Excess deposit growth in the banking system during the demonetisation period (i.e., November 11, 2016 to December 30, 2016) works out to 4-4.7 percentage points. If the period up to mid-February 2017 is taken into account to allow for some surge to taper off, excess deposit growth is in the range of 3.3-4.2 percentage points.. The liquidity boost resulting from the demonetisation announcement on November 8, 2016 has stayed with the banking sector a year after the event, helping banks reduce their high-cost deposits and boosting their current account and savings account (CASA) ratio. In this research paper researcher has tried to analyse the impact of demonetisation on indian banking industry.